Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa IAIN Langsa Untuk Berwirausaha - Hasibuan, Faisal (Lembaga Pengembangan Kinerja Dosen, 2022)
Based on the need for a profile of graduates who are qualified in the field of entrepreneurship, with the aim of achieving the learning targets of the curriculum, preliminary observations were designed which have led to the stages of this research. This descriptive research is arranged in such a way using quantitative methods, which will be carried out directly on the object under study. This is intended to obtain valid data needed, one of which is by using a questionnaire (questionnaire).The results in this study are first, there is a significant positive effect on the motivation variable on the variable interest in entrepreneurship in Islamic Banking students IAIN Langsa 2015 and 2016. The results of the T test which shows the t-count value is greater than the t-table value, namely of 7.620 > 1.98260. Second, there is no positive and significant effect on the self-efficacy variable on the variable interest in entrepreneurship in Islamic Banking students at IAIN Langsa class of 2015 and 2016. Third, there is a significant positive effect on the family environment variable on the variable of interest in entrepreneurship in the FEBI Islamic Banking IAIN Langsa students class 2015 and 2016. Fourth, there is a significant positive effect on the variables of motivation, self-efficacy, family environment simultaneously (together) on the variable interest in entrepreneurship in the FEBI Islamic Banking students of IAIN Langsa class of 2015 and 2016. This is evidenced by the results of the F test which shows the f value. count is greater than the f-table value, namely 145,097> 2.6.